Weight-for-length, early weight-gain velocity and atopic dermatitis in infancy and at two years of age: a cohort study - Teresa Løvold Berents; Karin Cecilie Lødrup Carlsen; Petter Mowinckel; Håvard Ove Skjerven; Leif Bjarte Rolfsjord; Live Solveig Nordhagen; Bente Kvenshagen; Jon Olav Gjengstø Hunderi; Maria Bradley; Per Medbøe Thorsby; Kai-Håkon Carlsen; Petter Gjersvik (BMC, 2017)
Abstract Background Overweight and atopic dermatitis (AD) are major health problems in most industrialised countries, but the relationship between overweight and AD in infants and young children is unclear. We investigated if weight-for-length at birth, in infancy and at two years, as well as early weight-gain velocity, are associated with the development of AD in early life. Methods Cohort study of infants (n = 642), all living in south-east Norway, hospitalized with acute bronchiolitis (n = 404) or recruited from the general population (n = 238), examined at mean age 5.1 months (enrolment) and at a two-year follow-up visit (n = 499; 78%) at mean age 24.6 months. Exposures were weight-for-length (g/cm) at birth, enrolment and two-year follow-up, and early weight-gain velocity (gram/month from birth to enrolment). Excessive weight-for-length was defined as weight-for-length >95th percentile of WHO child-growth standards. Data on weight-for-length at the three time points were obtained for 435, 428 and 473 children. AD was diagnosed according to the Hanifin & Rajka criteria or from a history of physician-diagnosed AD. We performed multivariate analyses with weight-for-length at birth, at enrolment and at the two-year follow-up visit and with early weight gain velocity for the endpoint AD at each visit. Results In adjusted analyses, excessive weight-for-length at enrolment was associated with concurrent AD (OR 3.03; 95% CI 1.23-7.50) and with AD at two years (OR 2.40; 1.11-5.17). In infants without AD, weight-for-length at enrolment increased the risk of AD at two years, with OR being 1.02 (95% CI 1.00-1.04) per increased gram/cm. AD at two years was not associated with concurrent excessive weight-for-length, nor was AD at any time associated with weight-for-length at birth or with early weight-gain velocity. Conclusions The results suggest that overweight in infancy may contribute to the development of AD in early life, highlighting the need for child health-care professionals to address potential overweight and atopic disease when advising infants' caregivers. Trial registration ClinicalTrials.gov number, NCT00817466 , EudraCT number, 2009-012667-34.